A Small Effort for Future Bonus Demography: Growing the Dream of Orphanage Children - Supeni Mapuasari; Mila Austria Reyes (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Indonesia is going to face bonus demography within 2030–2040. The productive people within those years will have the highest percentage of the population. Bonus demography will benefit the country if the young generation grows up with high motivation to create positive impacts. As the Indonesian Gini ratio (reflecting income inequality) is quite high, many orphanage houses exist to help the poor and yatim children live and grow as well as other normal families. A lot of social organizations build and operate orphanage houses, a place to fulfill physical needs and education. Nevertheless, society needs to support orphanage children to grow and reach their dreams. This community development is aimed at delivering motivation to orphanage children to be optimists and raise their dreams. This project was done at Panti Asuhan Rumah Berkat, Cikarang, and organized for delivering the material. The main purpose of the material is to raise hope to realize a future dream by taking small steps (studying) and moving consistently. This activity is written with the hope that there will be many duplications as the number of orphanage houses in Indonesia is numerous.